Analisis Frasa Idiomatik dalam Lirik Lagu “Dalam Diam” Karya Sal Priadi - Dewi, Sagita Tiara; Haryadi (P3M Politeknik Negeri Media Kreatif, 2026)
Idiomatic phrases play a crucial role in enriching Indonesian language expression, particularly in verbal art forms such as modern song lyrics. This research aims to identify idiomatic phrases in the song